2021
DOI: 10.3390/ma14061382
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Enhanced Release of Resveratrol from Mesoporous Silica Nanoparticles for Melanoma Therapy

Abstract: Chemotherapy has limited success in the treatment of malignant melanoma due to fast development of drug resistance and the low bioavailability of chemotherapeutic drugs. Resveratrol (RES) is a natural polyphenol with recognized preventive and therapeutic anti-cancer properties. However, poor RES solubility hampers its bioactivity, thus creating a demand for suitable drug delivery systems to improve it. This work aimed to assess the potential of RES-loaded mesoporous silica nanoparticles (MSNs) for human melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 85 publications
5
34
0
Order By: Relevance
“…Thus, the amount of crystalline resveratrol is mainly explained by steric factors, with higher matrix pore volume and diameter resulting in higher crystalline fraction and with a higher surface area yielding more drug molecules adsorbed as an amorphous surface layer, resulting in a lower crystalline phase fraction. Our results are in accordance with the literature data showing that the resveratrol encapsulation into mesopores of pristine MSN has only led to the amorphization of a part of polyphenol molecules [42].…”
Section: Physico-chemical Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the amount of crystalline resveratrol is mainly explained by steric factors, with higher matrix pore volume and diameter resulting in higher crystalline fraction and with a higher surface area yielding more drug molecules adsorbed as an amorphous surface layer, resulting in a lower crystalline phase fraction. Our results are in accordance with the literature data showing that the resveratrol encapsulation into mesopores of pristine MSN has only led to the amorphization of a part of polyphenol molecules [42].…”
Section: Physico-chemical Characterizationsupporting
confidence: 93%
“…Marinheiro et al reported that A375 melanoma cells are more sensitive to either resveratrol-loaded MSN formulation or free resveratrol than MNT-1 cells. Hence, they obtained IC 50 values of 21.1 µg/mL and 29.5 µg/mL for A375 cell line and MNT-1 cells after 48 h and 72 h of exposure, respectively [42]. Recently, Lin et al found that resveratrol inhibited proliferation, migration, and invasion while promoting apoptosis in human gastric cancer HGC-27 and AGS cells, and alleviated tumor size in vivo, greater effects being observed for resveratrol-loaded MSN than in the case of free polyphenol [45].…”
Section: Cytotoxicity Apoptosis and Cell Cycle Analysismentioning
confidence: 98%
“…Resveratrol has also been loaded in uniformly sized (~60 nm) phosphonate and amine modified MSNs in order to improve its in vitro antiproliferative and cytotoxic activity against a prostate cell line. The authors postulated that both phosphonate and amine mesoporous silica nanoparticles showed controlled release compared to the free molecule in 24 h whereas the former were also found to enhance its antiproliferative potential [ 383 ]. Mesoporous silica nanoparticles loaded with curcumin have also been fabricated as a potent anticancer agent [ 384 ].…”
Section: Inorganic-based Delivery Systemsmentioning
confidence: 99%
“…The nanocarriers have attractive textural features such as high surface area with more than 1100 m 2 /g and pore size ranging between 1.5–10 nm with different types of pore orderings. Other structured silicates are SBA-1, SBA-16, and KIT-6 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%